Khat chewing and associated factors among public secondary school students in Harar town, Eastern Ethiopia: a multicenter cross-sectional study - Nigussie, Kabtamu; Negash, Abraham; Sertsu, Addisu; Mulugeta, Abiy; Tamire, Aklilu; Kassa, Obsan; Abdeta, Tilahun; Dereje, Jerman (Frontiers in Psychiatry, 2023)
Background: Khat is a huge, evergreen tree that grows at high altitudes all throughout the Arabian Peninsula as well as in the region that stretches from eastern to southern Africa. Ethiopian teenagers frequently use khat, particularly among secondary school students. However, the study area lacks information on prevalence and its associated factors. Objective: To determine the prevalence of khat chewing and related factors among secondary school students in public schools in Harar, Eastern Ethiopia, in 2022. Method: A multicenter cross-sectional study design was employed from June 01-June 30, 2022, in three public secondary schools in Harar town among samples of 485. Systematic random sampling was used to choose the study sample. The data were gathered by self-administered questionnaires, and the Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST) was used to assess khat chewing. Epidata version 4.6 was used to enter data, while STATA version 14 was used to analyze it. To determine the factors related to Khat chewing multivariate logistic regression analysis was conducted, and statistical significance was determined at a 95% confidence level with a P-value under 0.05 Results: Out of a total of 485 eligible participants, 455 responded to this survey, giving a response rate of 93.8%. Overall, 33.2% (95% CI: 29.2%-37.6%) of the sample's participants reported currently chewing khat. Age ranged from 20-25 years (AOR= 2.04; 95% CI: 1.19-3.48), male students (AOR= 7.03; 95% CI: 4.35 -12.57), current alcohol user (AOR 6.48; 95% CI: 2.30-18.28), presence of chewer friends (AOR 3.86; 95% CI: 2.38-6.24), and depression (AOR 1.84, 95%CI:1.02-3.30), were strongly associated with Khat chewing at a p-value < 0.05. Khat chewing was very common among students in Eastern Ethiopia's public secondary schools. Ages 20 to 25 years old, being a male, current alcohol users, having chewer buddies, and depression are significantly linked to khat use. Thus, the School should therefore create and implement audience-specific behavioral change communication to deter and stop students from chewing Khat. Additionally, it's important to ban the selling of khat to young adults and adolescents, promote medical care for khat users, and foster peer advocacy for support services for khat users.